Evaluating Morphological Variability Of Artemisia Herba-alba Asso From Western Algeria - Maghni, B.; Adda, A.; Merah, O. (University of Eloued جامعة الوادي, 2017)
This work was interested on the study of the morphological variability of 120 individuals of Artemisia herba-alba Asso coming from three stations in western Algeria , which was assessed through 15 quantitative and qualitative characters. Analysis of variance (ANOVA) and hierarchical cluster analysis (HCA) results showed significant morphological variability inter and intra-population. This phenotypic variability is explained by a high genetic polymorphism determined at another genetic study that we conducted in parallel on individuals of the same site using molecular markers types ISSR.This study also revealed a large variability within A. herba alba which could help investigation on a large collection of individuals and therefore select the most efficient ecotypes for re-introduction this species in steppes and highlands of Algeria.
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Artemisia herba-alba Asso; Morphological variability;steppe;Algeria.